2022
DOI: 10.1002/app.53227
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid based on graphene nanoplatelets and carbon nanotubes obtained in a single‐step approach and its reinforcement effect in an epoxy matrix

Abstract: A hybrid based on graphene nanoplatelets and carbon nanotubes (G‐CNT) is obtained through direct exfoliation of graphite in a liquid medium, and tested as reinforcement material in epoxy resin. CNT act as exfoliation material in contact with graphite under ultrasound irradiation, and the thickness of graphite decreases to produce graphene nanoplatelets in an easy one‐step method. The morphology of the hybrid, is observed through transmission electron microscopy micrographs exhibiting delamination of graphite. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…By incorporating CNTs‐GO into the PVA polymer, the cross‐section of CNTs yarn/CNTs‐GO PVA showed a distinct helical structure (Figure 2e), wherein CNTs bundles possessed more connections (Figure 2h) among the integrated three‐dimensional networks formed by hybrid CNTs and GO materials. It has been reported that the CNTs‐GO three‐dimensional network was conducive to load transfer efficiency 26 . Differently, the cross‐sectional view of carboxyl CNTs yarn/CNTs‐GO PVA showed a tight, uniform, smooth helical structure, with comparatively shorter CNTs bundles compared with those of CNTs yarn/PVA and CNTs yarn/CNTs‐GO PVA (Figure 2f).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…By incorporating CNTs‐GO into the PVA polymer, the cross‐section of CNTs yarn/CNTs‐GO PVA showed a distinct helical structure (Figure 2e), wherein CNTs bundles possessed more connections (Figure 2h) among the integrated three‐dimensional networks formed by hybrid CNTs and GO materials. It has been reported that the CNTs‐GO three‐dimensional network was conducive to load transfer efficiency 26 . Differently, the cross‐sectional view of carboxyl CNTs yarn/CNTs‐GO PVA showed a tight, uniform, smooth helical structure, with comparatively shorter CNTs bundles compared with those of CNTs yarn/PVA and CNTs yarn/CNTs‐GO PVA (Figure 2f).…”
Section: Resultsmentioning
confidence: 87%
“…It has been reported that the CNTs-GO three-dimensional network was conducive to load transfer efficiency. 26 Differently, the cross-sectional view of carboxyl CNTs yarn/CNTs-GO PVA showed a tight, uniform, smooth helical structure, with comparatively shorter CNTs bundles compared with those of CNTs yarn/ PVA and CNTs yarn/CNTs-GO PVA (Figure 2f). As shown in the high-magnification SEM image (Figure 2i), the CNTs bundles entangled together, besides, more CNTs bridges were observed between the two bundles owing to that the functional group within carboxyl CNTs yarn could entangle more CNTs nanomaterials.…”
Section: Ftir Spectra and Morphologies Of Cnts Composite Yarnmentioning
confidence: 91%
“…The storage modulus and loss factor are important parameters to characterize the viscoelastic behavior of a polymer‐based material 46,47 . As shown in Figure 7a, the storage modulus ( E ′) of CBH/EP composites gradually increases with increasing CBH loading content.…”
Section: Resultsmentioning
confidence: 99%
“…The storage modulus and loss factor are important parameters to characterize the viscoelastic behavior of a polymer-based material. 46,47 As shown in Figure 7a, the storage modulus (E 0 ) of CBH/EP composites gradually increases with increasing CBH loading content. The E 0 of the composite loaded with 3.5 wt% CBH increases to 3.64 GPa, which is 48.57% higher than that of the EP matrix (2.45 GPa).…”
Section: Dynamic Mechanical Thermal Propertiesmentioning
confidence: 91%
See 1 more Smart Citation